Preserved physical fitness is associated with lower 1-year mortality in frail elderly patients with a severe comorbidity burden - Åhlund, Kristina (Clin Interv Aging, 2019)
INTRODUCTION: Physical deterioration in connection with a care episode is common. The aim of this study was, in frail elderly patients with a severe comorbidity burden, to analyze 1) the association between physical fitness measurements and 1-year mortality and 2) the association between preserved physical fitness during the first three months after discharge from emergency hospital care and 1-year prognosis. METHODS: Frail elderly patients (≥75 years) in need of inpatient emergency medical care were included. Aerobic capacity (six-minute walk test, 6MWT) and muscle strength (handgrip strength test, HS) were assessed during the hospital stay and at a three-month follow-up. The results were analyzed using multivariate Cox regression; 1) 0–12-month analysis and 2) 0–3-month change in physical fitness in relation to 1-year mortality. The analyses were adjusted for age, gender, comorbidity and frailty. RESULTS: This study comprised 408 frail elderly hospitalized patients of whom 390 were evaluable (mean age 85.7 years, Charlson’s index mean 6.8). The three-month mortality was 11.5% and the 1-year mortality was 37.9%. After adjustments, the Cox-regression analysis showed that both 6MWT and HS were associated with 1-year mortality, HR(6MWT) 3.31 (95% CI 1.89–5.78, p>0.001) and HR(HS) 2.39 (95% CI 1.33–4.27, p=0.003). The 0–3-month change in the 6MWT and the HS were associated with 1-year mortality, where patients who deteriorated had a poorer prognosis than those with improved fitness, HR(6MWT) 3.80 (95% CI 1.42–10.06, p=0.007) and HR(HS) 2.21 (95% CI 1.07–4.58, p=0.032). CONCLUSION: In frail elderly patients with a severe comorbidity burden, physical fitness in connection with emergency hospital care was independently associated with 1-year mortality. Moreover, a change in physical fitness during the first months after hospital care was important for the long-term prognosis. These results emphasize the importance of providing hospital care designed to prevent physical deterioration in frail elderly patients.